Emotional education in teacher training and evaluation - Guerrero-Guillén, Roxana; Montenegro-Robelo, Giselle; Pereira-Martín, Tamara (Scientific journal of social studies, 2023)
This article highlights the significance of emotional and social skills, commonly known as socio-emotional skills, as crucial tools for the holistic development of individuals. Furthermore, it emphasizes the importance of emotional education as a fundamental requirement for teacher training and practice. This literature review article provides a documentary review of the primary concepts related to emotional and social competencies as essential tools for the comprehensive development of individuals and the impact of developing emotional and social skills on teachers. In conclusion, it can be asserted that both teacher training and evaluation on socio-emotional issues are indispensable for enhancing the quality of education across all educational levels and meeting the societal demands for building a better world.